After the destruction of giant buddha statues in bamiyan (Afghanistan) in 2001 : A UNESCO's emergency activity for the recovering and rehabilitation of cliff and niches - Margottini, Claudio (Natural Science in Archaeology, 2014)
This work reports on a real adventure in earth science and conservation, dealing with the UNESCO's emergency activities implemented in Bamiyan (Central Afghanistan) for the recovery and rehabilitation of the cliff and niches after the destruction of the two famous Giant Statues in 2001.   Since 2002 an international effort has been made to understand the geological characteristics of the area, the mechanical properties of local materials, petro-geophysical and sedimentological details as well as the historical and geological evolution of the Statues and cliff. Taken together, this information serves as a basis for the recovery and rehabilitation of the cliff and niches and is presented in detail.